2014
DOI: 10.1152/physiol.00042.2013
|View full text |Cite
|
Sign up to set email alerts
|

The Myoendothelial Junction: Connections That Deliver the Message

Abstract: A vast amount of investigation has centered on how the endothelium and smooth muscle communicate. From this evidence, myoendothelial junctions have emerged as critical anatomical structures to regulate heterocellular cross talk. Indeed, there is now evidence that the myoendothelial junction serves as a signaling microdomain to organize proteins used to facilitate vascular heterocellular communication. This review highlights the evolving role of myoendothelial junctions in the context of vascular cell-cell comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 67 publications
2
68
0
Order By: Relevance
“…810 The MEJs are anatomical hallmarks where primarily endothelium (depending on vascular bed) breaks through the internal elastic lamina (IEL) and comes into close apposition with the overlying smooth muscle cells, forming gap junctions for direct cell-cell communication (reviewed in 11 ). The MEJs are found in resistance arteries down to terminal arterioles, with little to no MEJs identified in conduit arteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…810 The MEJs are anatomical hallmarks where primarily endothelium (depending on vascular bed) breaks through the internal elastic lamina (IEL) and comes into close apposition with the overlying smooth muscle cells, forming gap junctions for direct cell-cell communication (reviewed in 11 ). The MEJs are found in resistance arteries down to terminal arterioles, with little to no MEJs identified in conduit arteries.…”
Section: Introductionmentioning
confidence: 99%
“…The MEJs are found in resistance arteries down to terminal arterioles, with little to no MEJs identified in conduit arteries. 11 These cellular structures provide a distinct microenvironment at the interface between smooth muscle and endothelium where a number of proteins have been shown to be localized and enriched to influence heterocellular cross talk in the arterial blood vessel wall. Indeed, we have found that eNOS is polarized across vascular beds at MEJs 7 , and more recently have demonstrated that endothelial cells in resistance arteries synthesize and express hemoglobin α (Hb α) which co-localizes with eNOS at MEJs where it functions to regulate NO diffusion to vascular smooth muscle during α 1 -adrenergic-dependent vasoconstriction 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the next 50 years, research into the functional roles of these projections revealed their importance in second messenger communication and electrical signaling within the vascular wall. MEJs tend to have a greater presence in arteries with a smaller luminal size [2, 3], which allows these vessels a faster endothelial response to second messengers originating in the smooth muscle [4] by providing a platform for the organization and localization of signaling proteins [5]. …”
Section: Introductionmentioning
confidence: 99%
“…(102) Under 100nm in diameter, their distribution is heterogeneous throughout the vasculature, with a higher concentration located in smaller caliber arteries as opposed to the larger proximal arteries. (103) To date, only Cx37, Cx40, and Cx43 have been identified within MEPs, with Cx40 shown to be involved in endothelial-derived hyperpolarization (EDH)-mediated vasodilation.…”
Section: Regional Vessel Communicationmentioning
confidence: 99%